Overcoming Personal Biases: A key for Effective Performance Appraisal - Shah, Nawroz Bibi Zeenat; Idrees, Sobia; Zafar, Misbah (International Journal of Endorsing Health Science Research, 2015)
Performance appraisal is a very challenging task for a manger that needs expertise along with commitment to fulfill the process in a fair and transparent manner. There are some standards, which are very essential for motivation of the staff and organizational growth. Performance appraisal does not only mean evaluating the performance of a staff but it provides a platform to overcome the deficiencies and set plan for the staff with mutual understanding. The most neglected part of performance appraisal process is setting SMART goals for the staff by a manager with mutual understanding. Many factors hinder the process of appraisal that include; organizational culture, predetermined budgetary constraints, capability of manger/supervisor and lack of training opportunities by human resource department. These factors may lead to dissatisfaction among staff and in the long run develops a mindset with negative image for the entire process. Maslow’s needs theory should be kept in mind to evaluate the performance of a staff as all human have common needs but with different desires to satisfy their hierarchy of needs.